A tour of ethnic food store - Nelson, Melanie; Learning Zone Express ([S.l.] : The Learning Zone, 2002)
Explores the ethnic markets of Mexican, Italian and Chinese . These authentic markets have the ordinary to the unfamiliar food items. Travel with dynamic and engaging Chef Andrew Zimmern on this food journey
Title from title screen
Host : Andrew Zimmeran
Keywords: Cookery; Cookery, Italian; Cookery, Mexican; Cookery, Chinese